The relationship between internal audit and internal control in Malaysian cooperatives: the moderating effect of risk-management training / Shamsul Anuar Abd Rahim - Abd Rahim, Shamsul Anuar (2021)
Cooperatives make the crucial third engine of growth in most countries' economy after the public and the private sectors. This study's first research objective examines the relationship of internal audit effectiveness characteristics on internal control among Malaysian cooperatives. The second research objective is to examine and visualise the adapted COSO internal control components and its effectiveness objectives among Malaysian cooperatives and present their internal control effectiveness achievement. Using the COSO internal control framework, the cooperative’s internal controls effectiveness is measured by relying on internal auditor’s assessment rather than utilising the material weakness statement in the financial statement. This evaluation method is considered more purposeful for cooperatives that do not have the requirement to disclose their material weaknesses. The result of the second research objective is used as the dependent variable to satisfy the first research objective. The third research objective is to examine the moderating effect of the cooperative’s staff's risk-management training on the relationship between internal audit effective characteristics and internal control effectiveness among Malaysian cooperatives. A survey is randomly administered to 234 Cooperatives with annual revenues of more than RM800,000.00 using a self-administered questionnaire and 126 cooperatives have responded (53.8% response rate). Latest cooperatives information is collected from Malaysian Co-operative Societies Commission (MCSC), a governing body for Malaysian cooperatives. This study has utilised the Kohonen’s self-organising map, a clustering method for the second research objective and the Partial Least Squares Structural Equation Modelling (PLS-SEM) for the other two research objectives. The clustering analysis reveals four levels of internal control effectiveness in Malaysian cooperatives, which less than one-fourth of the cooperatives are considered having effective internal controls. The four alternative levels of internal control effectiveness are the highest internal control effectiveness, low efficiency and effectiveness of activities, low reliability of financial information, and the lowest internal control effectiveness. The PLS-SEM analysis shows that internal audit accessible to senior management significantly influences the effectiveness of Malaysian cooperatives' internal control. The other variables of internal audit characteristics do not influence the cooperative’s internal controls effectiveness. Testing the moderator influence, riskmanagement training of the cooperatives' staff, is found to moderate the relationship between internal audit budget and cooperatives’ internal control effectiveness. In terms of practical implication, the findings show that internal audit effective characteristics have some influence on cooperative internal control effectiveness. Ensuring regulation, providing support to a cooperative internal audit, forming an independent internal audit unit and having effective monitoring from MCSC would further enhance internal audit purposes. The findings have some significances on those responsible for assessing and improving the cooperative’s internal control.